TELAAH KITAB AL-SUNNAH QABLA AL-TADWĪN KARYA M. ‘AJJAJ AL-KHATIB - Ummi Kalsum Hasibuan; Sartika Suryadinata (Ushuluna: Jurnal Ilmu Ushuluddin, 2018)
This article explores the book of al-Sunnah Qabla al-Tadwīn by M. Ajjaj al-Khatib, an Islamic thinker who is an expert in the field of hadith science, coming from the city of Damascus. The purpose of this paper is to uncover, study and find out about the biography of M. Ajjaj al-Khatib and how systematic and fleeting about discussing the contents of the book al-Sunnah Qabla al-Tadwin then related to the rebuttal of Ajjaj al-Khatib sunnah. Then do not need attention about the advantages and disadvantages that exist in the book. The method used in this paper is a descriptive-text analysis method for the book as-Sunnah Qabla Tadwīn by using a supported book.